2016
DOI: 10.1016/j.virol.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in VP1 and 3A proteins improve binding and replication of rhinovirus C15 in HeLa-E8 cells

Abstract: Viruses in the rhinovirus C species (RV-C) can cause severe respiratory illnesses in children including pneumonia and asthma exacerbations. A transduced cell line (HeLa-E8) stably expressing the CDHR3-Y529 receptor variant, supports propagation of RV-C after infection. C15 clinical or recombinant isolates replicate in HeLa-E8, however progeny yields are lower than those of related strains of RV-A and RV-B. Serial passaging of C15 in HeLa-E8 resulted in stronger cytopathic effects and increased (≥ 10-fold) viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
2
29
1
Order By: Relevance
“…The initially strong heparin-binding variant acquired an additional mutataion, which confers weak heparin-binding phenotype and high virulence. Furthermore, attenuation of viruses via cell culture adaptation mediated by glycosaminoglycans (including HS) has been reported for many Flaviviridae (e.g., Japanese encephalitis virus, Murray Valley encephalitis virus, West Nile virus, and Dengue virus) [87][88][89][90], Togaviridae (Sindbis virus, Venezuelan equine encephalitis virus, Tickborne encephalitis virus, and Chikungunya virus) [91][92][93][94], and Picornaviridae (human Rhinovirus (HRV) C15, HRV89, and foot and mouth disease virus) [95][96][97]. In addition to this trapping effect, Fujii et al [85] reported that HS-binding strains are more easily neutralized by antibodies than HSnonbinding strains.…”
Section: Hsmentioning
confidence: 99%
“…The initially strong heparin-binding variant acquired an additional mutataion, which confers weak heparin-binding phenotype and high virulence. Furthermore, attenuation of viruses via cell culture adaptation mediated by glycosaminoglycans (including HS) has been reported for many Flaviviridae (e.g., Japanese encephalitis virus, Murray Valley encephalitis virus, West Nile virus, and Dengue virus) [87][88][89][90], Togaviridae (Sindbis virus, Venezuelan equine encephalitis virus, Tickborne encephalitis virus, and Chikungunya virus) [91][92][93][94], and Picornaviridae (human Rhinovirus (HRV) C15, HRV89, and foot and mouth disease virus) [95][96][97]. In addition to this trapping effect, Fujii et al [85] reported that HS-binding strains are more easily neutralized by antibodies than HSnonbinding strains.…”
Section: Hsmentioning
confidence: 99%
“…Capitalizing on this concept, the RV-C receptor hunt switched focus to the Tyr529 variant and was almost instantly rewarded with fully infectious virus amplification systems. The direct and immediate experimental outcomes included tissue culture-adapted virus strains for enhanced growth (12) and satisfactory virus isolation for a high-resolution cryo-electron microscopy (cryoEM) determination of the RV-C15a capsid structure (13). Since that point, RV-C and CDHR3 investigations have been necessarily coevolving.…”
Section: Rv-cmentioning
confidence: 99%
“…In addition, some respiratory viruses, such as RVs from species C, grow poorly in standard cell lines. 11 In this respect much effort has been dedicated to develop more representative models, such as airway epithelia reconstituted from primary cells isolated from nasal or bronchial surgeries. These air-liquid interface Abbreviations used dpi: Days after infection EV: Enterovirus HCoV: Human coronavirus HTS: High-throughput RNA sequencing IP-10: Interferon-inducible protein 10 LDH: Lactate dehydrogenase MCC: Mucociliary clearance qPCR: Real-time quantitative PCR RSV: Respiratory syncytial virus RV: Rhinovirus TEER: Transepithelial electrical resistance tissue-culture systems have been validated for the study of respiratory viruses, such as RSV, 12 influenza, 13 human coronaviruses (HCoVs), and RVs.…”
mentioning
confidence: 99%